Naturally Acquired Antibody Response to Malaria Transmission Blocking Vaccine Candidate Pvs230 Domain 1 - Tentokam, Bergeline C. Nguemwo; Amaratunga, Chanaki; Alani, Nada A. H.; MacDonald, Nicholas J.; Narum, David L.; Salinas, Nichole D.; Kwan, Jennifer L.; Suon, Seila; Sreng, Sokunthea; Pereira, Dhelio Batista; Tolia, Niraj H.; Fujiwara, Ricardo T.; et al. (Frontiers in Immunology, 2019)
Plasmodium vivax malaria incidence has increased in Latin America and Asia and is responsible for nearly 74.1% of malaria cases in Latin America. Immune responses to P. vivax are less well characterized than those to P. falciparum, partly due to the fact that P. vivax is more difficult to cultivate in the laboratory. While antibodies are known to play an important role in P. vivax disease control, few studies have assessed humoral responses to liver or blood stage P. vivax parasites, and none have evaluated responses to P. vivax sexual stage antigens. We collected sera or plasma samples from 70 subjects from Brazil and 79 from Cambodia to assess antibody responses to domain I of the gamete stage protein Pvs230 (Pvs230D1M). We found that 27.1% (19/70) of subjects from Brazil presented antibody response to Pvs230D1M antigen while in Cambodia this response was found in 26.6% (21/79) of the subjects. The most frequent subclasses elicited in response to Pvs230D1M were IgG1 and IgG3. Although age did not correlate significantly with Pvs230D1M antibody levels overall, we observed significant differences between major strata. Hemoglobin concentration inversely correlated with Pvs230D1M antibody levels in Brazil, but not in Cambodia. Additionally, we analyzed the antibody response against Pfs230D1M, the P. falciparum orthologue of Pvs230D1M. We detected antibody to Pfs230D1M in 7.2% of Brazilian and 16% of Cambodian P. vivax-infected subjects. Depletion of Pvs230D1M IgG did not impair the high response to Pfs230D1M, suggesting a pre-exposure to P. falciparum, or co-infection. We also analyzed levels of IgG generated in response to PvCSP (11.4% in Brazil and 67.1% in Cambodia) and to PvDBP-RII (67.1% in Brazil and 48.1% in Cambodia), whose titers also inversely correlated with hemoglobin concentration only in Brazil. These data establish patterns of seroreactivity to sexual stage P. vivax antigen show similar antibody responses among P. vivax-infected donors from regions of differing transmission intensity in Brazil and Cambodia.